A human-centric approach to communication language and its impacts on stakeholders and brand image: Identifying how BRAC stands out in the development sector. - Islam, Syeda Tasnim (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.